Environmental Conservation Education in the Qur’an Perspective - Syamsuriana Basri; Rahmi Damis; Mardan (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2023)
This study aims to describe an overview of the concept of environmental conservation in the Koran, the urgency and conservation efforts in the Qur’an. This study uses a qualitative-descriptive research method with library research techniques. The results of the study show that environmental preservation in the Qur'an, which teaches us always to protect the environment, is contained in several verses, including QS Ar-Rum: 41-42 about Prohibition of Making Damage on Earth, QS Al A'raf: 56-58 about Caring for the environment. and QS Al-Baqarah (2): 60 about Allah providing sustenance to all humans and forbidding humans to make mischief on this earth. Then the urgency of environmental preservation, according to the Qur'an, is explained that the environment is nature where humans are in it must be preserved. This is based on human dependence on nature, and everything is created in balance, everything in nature is for the benefit of humans and nature as a source of sustenance and the efforts recommended by the Qur'an in preserving the surrounding environment, among others; planting trees for reforestation, managing dead and vacant land, keeping the environment clean and avoiding destruction and maintaining the balance of nature.